Practical classification accuracy of sequential data using neural networks - Mamoru Mimura (Machine Learning with Applications)
Many existing studies on neural network accuracy utilize datasets that may not always reflect real-world conditions. While it has been demonstrated that accuracy tends to decrease as the number of benign samples increases, this effect has not been quantitatively assessed within neural networks. Moreover, its relevance to security tasks beyond malware classification remains unexplored. In this research, we refined the metric to evaluate the degradation of accuracy with an increased number of benign samples in test data. Utilizing both standard and specific neural network models, we conducted experiments to adapt this metric to neural networks and various feature extraction techniques. Using the FFRI dataset, comprising 150,000 malware and 400,000 benign samples, along with the URL dataset, containing 3143 malicious and 106,545,781 benign samples, we increased benign samples in the test set while keeping the training set’s malicious and benign samples constant. Our findings indicate that neural networks can indeed overestimate their accuracy with a smaller count of benign samples. Importantly, our refined metric is not only applicable to neural networks but is also effective for other feature extraction methods and security tasks beyond malware detection.